Patterns of care for metastatic renal cell carcinoma in Australia. (21st July 2015) - Day, Daphne; Kanjanapan, Yada; Kwan, Edmond; Yip, Desmond; Lawrentschuk, Nathan; Andrews, Miles; Davis, Ian D; Azad, Arun A; Rosenthal, Mark; Wong, Shirley; Johnstone, Alice; Gibbs, Peter; et al.
Abstract : Objective: To examine the patterns of care and outcomes for metastatic renal cell carcinoma (mRCC) in Australia, where there are limited reimbursed treatment options. In particular, we aim to explore prescribing patterns for first‐line systemic treatment, the practice of an initial watchful‐waiting approach, and the use of systemic treatments in elderly patients. Subjects/Patients and Methods: Patients with mRCC undergoing treatment between 2006 and 2012 were identified from four academic hospitals in Victoria and Australian Capital Territory. Demographic, clinicopathological, treatment, and survival data were recorded by chart review. Descriptive statistics were used to report findings. Survival was estimated by the Kaplan–Meier method and compared using the log‐rank test. The study was supported by a grant from Pfizer Australia. Results: Our study identified 212 patients with mRCC for analysis. Patients were predominantly of clear cell histology (75%), Eastern Cooperative Oncology Group performance status <2 (67%) and with favourable/intermediate Memorial Sloan‐Kettering Cancer Center risk (68%). The median age at diagnosis was 61 years. In all, 163 (77%) patients received first‐line systemic therapy, while 49 (23%) received best supportive care (BSC). The most frequently used first‐line treatment was sunitinib (125 patients, 77%). Patients who received sunitinib had a median overall survival (OS) of 27.6 months. In all, 43% of patients who received sunitinib underwent a watchful‐waiting period of >90 days before initiating treatment; these patients had a median OS of 56.3 months. Elderly patients (50 patients aged ≥70 years) were more likely to receive BSC alone than younger patients (46% vs 16%, P < 0.001). Of those who received systemic therapy, elderly patients were also more likely to have upfront dose reductions (30% vs 8%, P = 0.03). Conclusion: Our study of patients with mRCC treated in Australian centres showed that sunitinib was the most commonly prescribed systemic treatment between 2006 and 2012, associated with survival outcomes similar to pivotal studies. We also found that an initial watchful‐waiting approach is commonly adopted without apparent detriment to survival. And finally, we found that age has an impact on the prescribing of systemic therapy.